2010
DOI: 10.3179/jjmu.37.491
|View full text |Cite
|
Sign up to set email alerts
|

Relation between myocardial blood volume and left ventricular contractile reserve in patients with dilated cardiomyopathy

Abstract: tion, but it signifi cantly correlated with percent change in LVEF during dobutamine stress echocardiography r 0. 54 , p 0. 01 . Myocardial histomorphometric features in patients with DCM conceivably cause the reduction in myocardial blood volume, being related to the depressed contractile reserve. Conclusion : Myocardial blood volume measured by MCE was associated with LV con tractile reserve in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was revealed that myocyte diameter and interstitial fibrosis strongly correlated with change in the wall motion score index, followed by the change in LV ejection fraction. Recently, Yamada S, et al invetigated the association between myocardial blood volume and LV contractile reserve in 21 DCM patients using myocardial contrast echocardiography [40]. Myocardial blood volume was not correlated with any parameters of resting LV function, but significantly correlated with percent increase in LV ejection fraction during dobutamine stress testing.…”
Section: Latest Findings About Contractile Reservementioning
confidence: 99%
“…It was revealed that myocyte diameter and interstitial fibrosis strongly correlated with change in the wall motion score index, followed by the change in LV ejection fraction. Recently, Yamada S, et al invetigated the association between myocardial blood volume and LV contractile reserve in 21 DCM patients using myocardial contrast echocardiography [40]. Myocardial blood volume was not correlated with any parameters of resting LV function, but significantly correlated with percent increase in LV ejection fraction during dobutamine stress testing.…”
Section: Latest Findings About Contractile Reservementioning
confidence: 99%